2009
DOI: 10.1093/eurpub/ckp001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and cost-effectiveness of screening for Hepatitis C virus infection

Abstract: HCV screening and early treatment have the potential to improve average life-expectancy, but should focus on populations with elevated HCV prevalence to be cost-effective. Further research on the long-term health-economic impact of HCV screening when combined with appropriate monitoring strategies in different European health care systems is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 40 publications
2
45
1
Order By: Relevance
“…303 Plunkett and Grobman 304 found that screening pregnant women was not cost-effective. They assumed a 1% seroprevalence of hepatitis C virus and 48 weeks of treatment with pegylated interferon and ribavirin, but they calculated only direct costs.…”
Section: Relative Benefits and Harms Of Treatmentmentioning
confidence: 99%
“…303 Plunkett and Grobman 304 found that screening pregnant women was not cost-effective. They assumed a 1% seroprevalence of hepatitis C virus and 48 weeks of treatment with pegylated interferon and ribavirin, but they calculated only direct costs.…”
Section: Relative Benefits and Harms Of Treatmentmentioning
confidence: 99%
“…Successful treatment prevents secondary infections to HIV-positive sexual contacts and could possibly prevent spill-over to the HIV-negative population [31]. In contrast to HCV screening of the general population, HCV screening of groups with an elevated risk, like IDU, is cost-effective [52]. HIV-infected MSM have now also been recognised as a high risk group for HCV infection.…”
Section: Preventive Measures Against Viral Hepatitis In Msmmentioning
confidence: 99%
“…Successful eradication of HCV has been shown to improve the prognosis of HCV-induced liver disease and reduce the associated mortality (23,27). Hence, to adequately screen individuals with an active infection is a crucial issue in areas where HCV is endemic (24).…”
mentioning
confidence: 99%